Comparison of Nutrient Digestibility of Bligon and Kejobong Goats Fed by King Grass and Peanut Straw - Chusnul Hanim; Lies Mira Yusiati; I Gede Suparta Budisatria; Fandi Widya Rachman (Buletin Peternakan, 2020)
This experiment aimed to determine the nutrient digestibility of Bligon and Kejobong goats fed by king grass and peanut straw. The sample used was 6 to 8 months of five male Bligon goats, and five male Kejobong goats with the initial body weight of 15 to 20 kg and placed in separated metabolism cages. The diet and water were supplied ad libitum. This experiment was done in 14 days of adaptation period and seven days of the collection period. In the collection period, samples of feed, refusal feed, and feces were collected to get the chemical content includes dry matter (DM), organic matter (OM), ether extract (EE), crude fiber (CF), crude protein (CP), nitrogen-free extract (NFE), and total digestible nutrient (TDN). The data obtained were subjected to a T-test analysis. Results showed that nutrients intake, digested nutrient as well as nutrient digestibility of Bligon and Kejobong goats were not significantly different. However, Kejobong goats had EE and CP intake of 15.42% and 14.02%, digested DM, OM, and NFE of 16.29%, 15.71%, and 13.93% respectively, as well as NFE digestibility 4.37% higher than those Bligon goats (P< 0.05). Therefore, there was no difference in nutrient intake, digested, and digestibility of nutrients in Bligon and Kejobong goats fed by king grass and peanut straw. However, Kejobong goats appeared to have higher EE and CP intake, as well as digested and digestibility of DM, OM, and NFE than Bligon goats.